Precompetitive state anxiety in judo - Montero Carretero, Carlos; Moreno-Murcia, Juan A.; González Ponce, Inmaculada; Pulido González, Juan J.; Cervelló Gimeno, Eduardo M. (Revista de Artes Marciales Asiáticas, 2012)
Aim: The objective of this study was to analyze the psychometric properties of the Competitive State Anxiety Inventory-2 (CSAI-2) in Spanish judokas, and calculate differences in pre-competitive state anxiety due the sport level, age and gender. We analyze these relationships using a multidimensional anxiety perspective. Method: A sample of 128 judokas from amateur to high performance level participated in our study. The intensity and directional somatic anxiety, cognitive anxiety and self confidence of the CSAI-2 were measured. Results: The results show that the questionnaire administered showed acceptable psychometric properties, and there are differences in directional somatic and cognitive anxiety for age, and in intensity self confidence for sport level. The implications of these findings for the process of training and competition are discussed in the document.